Heidegger e o problema da origem da negatividade a partir do fenômeno do nada - Silva, Taciane Alves da (2020)
Nowhere else in the itinerary of Being and Time (1927) does Heidegger explicitly problematize the status of the nothing inherent in the structure of being of human existence when, from the notion of nullity, he recognizes in § 58 the unfounded (finite) character of Dasein. Regarding the clarification of nothingness, negativity (Nichtheit), latent in the existential structure of nullity, as an index of finitude, the ultimate meaning and significance of both are left, in Being and Time, as a task to be accomplished. Based on this diagnosis, this thesis proposes to investigate the ontological-metaphysical meaning of the phenomenon of nothingness, starting from the hypothesis that the problem can be taken as a guiding thread to understand a significant part of Heidegger's investigative path, mainly the path that extends from 1912 to 1939. It is intended to maintain that such a conducting thread has a fundamental and systematic character, insofar as, to be elucidated, it demands the determination of the status of the relationship between ontology, metaphysics and logic in the Heideggerian thought itinerary. Thus, far from being, at first sight, a circumstantial concern regarding the leitmotiv of Heidegger's thought, Seinsfrage, the question of nothingness and finitude would be central to the development, subsequent to the publication of SZ, of his metaphysics project. As a consequence, in raising the problem of the origin of negation, the concept of nothing would allow to establish the place occupied by logic itself within ontology and metaphysics. It is precisely the problem of the sense of nothingness that, in his historical-deconstructive record, allows Heidegger's critical confrontation (Auseinandersetzung) with Hegel, since, as an essential theme, negativity is investigated both in the Hegelian system, which represents the consummation of the history of Western metaphysics, as well as the history of metaphysics in general. In this sense, in spite of Heidegger's thematization of nothingness as a finiteness of being apparently opposed to the infinite power of negativity in the Hegelian logical-metaphysical system, we intend to maintain that there is a deep affinity between Hegel's and Heidegger's positions. If this hypothesis of an assumption common to both is correct, it will be possible not only to understand the scope of the problem opened by the concept of nothing in the Heideggerian Denkweg, but also to open a perspective, not explained by Heidegger, to thematize the very origin of nothing from its anthropogenic character.